Internal Control, Anti-Fraud Awareness, and Prevention of Fraud - Fitri Yani Jalil (ETIKONOMI, 2018)
Fraud is a serious threat to the organization and should prevent as early as possible. The prevention and detection of fraud is the responsibility of management. The fraud experts estimate that the fraud that has revealed is a small part of all the actual fraud that occurred. Therefore, the main effort is on prevention. This study aims to determine the effect of internal controls and anti-fraud awareness in the prevention of fraud. The samples used were employees of UIN Syarif Hidayatullah Jakarta. Data were analyzed using multiple regressions. The results showed that the internal control does not affect the prevention of fraud. Meanwhile, the anti-fraud awareness significant positive effect on the prevention of fraud. The results of this study are not yet entirely following the conditions at UIN Syarif Hidayatullah Jakarta. UIN Syarif Hidayatullah Jakarta has the concept of internal control and fraud prevention is good, but not yet implemented correctly by all parties. There are still some things that need to be improved practice, for example regarding employee performance evaluation, and program promotion of employees.DOI: 10.15408/etk.v17i2.7473